2019
DOI: 10.3390/nu11040903
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Famine During Early Life and Abdominal Obesity in Adulthood: Findings from the Great Chinese Famine During 1959–1961

Abstract: Undernutrition during early life may lead to obesity in adulthood. This study was conducted to examine the relationship between famine exposure during early life and the risk of abdominal obesity in adulthood. A total of 18,984 and 16,594 adults were surveyed in 2002 and 2010–2012 in two nationally representative cross-sectional surveys, namely China Nutrition and Health Survey, respectively. The risk of abdominal obesity was evaluated for participants born during 1956–1961 and compared with that of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
(47 reference statements)
4
33
3
Order By: Relevance
“…An increased waist to height ratio among adults was observed in the present study after early-life exposure to famine. The finding was consistent with other studies conducted in China [31], Dutch [26], and Nigeria [48]. This could be due to intrauterine nutritional insult, which brings developmental adaptations that permanently change the body structure and function and increases the risk of intra-abdominal fat deposition in later life [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An increased waist to height ratio among adults was observed in the present study after early-life exposure to famine. The finding was consistent with other studies conducted in China [31], Dutch [26], and Nigeria [48]. This could be due to intrauterine nutritional insult, which brings developmental adaptations that permanently change the body structure and function and increases the risk of intra-abdominal fat deposition in later life [22].…”
Section: Discussionsupporting
confidence: 91%
“…Findings from an earlier investigation of famine in early life and anthropometric indices of adulthood have been documented in Dutch [25][26][27][28][29] and Chinese [30][31][32][33] birth cohorts; however, the findings were varied. There is lack of information on the long-term consequences of earlylife exposure to famine in Ethiopia, a country with an unsettled situation with ongoing maternal and childhood malnourishment.…”
Section: Introductionmentioning
confidence: 99%
“…AAD was considered as a disorder of oxidative stress, and basic research indicated that oxidative stress played an important role in thoracic aortic aneurysms [26]. Third, exposure to famine during early life was associated with increased risks of obesity in adulthood [27], and obesity was signi cantly linked with increased visceral, perivascular, and epicardial adipose tissue [28]. A previous study demonstrated that increased epicardial adipose tissue thickness was correlated with AAD [29].…”
Section: Discussionmentioning
confidence: 99%
“…AAD was considered as a disorder of oxidative stress, and basic research indicated that oxidative stress played an important role in thoracic aortic aneurysms [35]. Third, exposure to famine during early life was associated with increased risks of obesity in adulthood [36], and obesity was signi cantly linked with increased visceral, perivascular, and epicardial adipose tissue [37]. A previous study demonstrated that increased epicardial adipose tissue thickness was correlated with AAD [38].…”
Section: Discussionmentioning
confidence: 99%